Diagnostic efficacy of O-RADS in benign and malignant ovarian tumors and influencing factors for ovarian malignancy - WANG Rongling, JIANG Yushan, TANG Wanqing, YANG Zongli (精准医学杂志, 2024)
Objective To explore the diagnostic value of the ovarian-adnexal reporting and data system (O-RADS) in differentiating between benign and malignant ovarian tumors, and to analyze risk factors for malignant ovarian tumors. Methods The clinical data of 417 patients with ovarian tumors diagnosed by pathology were retrospectively analyzed. With pathological results as the gold standard, the patients were divided into malignant group and benign group. The clinical data of the two groups were compared. At the same time, the patients were classified according to ultrasound characteristics and O-RADS. A receiver operating characteristic (ROC) curve was used to analyze the diagnostic efficacy of O-RADS. Results The univariable and mul-tivariable analyses showed that the risk factors for ovarian malignancy included cyst wall thickness ≥3 cm, solid components, blood flow score of 3-4 points, ascites, and peritoneal nodules (P<0.05). Compared with O-RADS 5, using O-RADS 4-5 to diagnose ovarian malignancy significantly increased the sensitivity, accuracy, and area under the ROC curve (χ2=6.28-18.84,P<0.05). Conclusion O-RADS can well differentiate between benign and malignant ovarian tumors. When using O-RADS 4-5 to indicate a high risk of ovarian malignancy, the diagnostic efficacy is best.